Brain Oxygen Extraction Is Differentially Altered by Alzheimer's and Vascular Diseases. Issue 6 (21st June 2020) - Jiang, Dengrong; Lin, Zixuan; Liu, Peiying; Sur, Sandeepa; Xu, Cuimei; Hazel, Kaisha; Pottanat, George; Darrow, Jacqueline; Pillai, Jay J.; Yasar, Sevil; Rosenberg, Paul; Moghekar, Abhay; et al.
Abstract : Background: Alzheimer's disease and vascular cognitive impairment (VCI), as well as their concurrence, represent the most common types of cognitive dysfunction. Treatment strategies for these two conditions are quite different; however, there exists a considerable overlap in their clinical manifestations, and most biomarkers reveal similar abnormalities between these two conditions. Purpose: To evaluate the potential of cerebral oxygen extraction fraction (OEF) as a biomarker for differential diagnosis of Alzheimer's disease and VCI. We hypothesized that in Alzheimer's disease OEF will be reduced (decreased oxygen consumption due to decreased neural activity), while in vascular diseases OEF will be elevated (increased oxygen extraction due to abnormally decreased blood flow). Study Type: Prospective cross‐sectional. Population: Sixty‐five subjects aged 52–89 years, including 33 mild cognitive impairment (MCI), 7 dementia, and 25 cognitively normal subjects. Field Strength/Sequence: 3T T2 ‐relaxation‐under‐spin‐tagging (TRUST) and fluid‐attenuated inversion recovery imaging (FLAIR). Assessment: OEF, consensus diagnoses of cognitive impairment, vascular risk factors (such as hypertension, hypercholesterolemia, diabetes, smoking, and obesity), cognitive assessments, and cerebrospinal fluid concentration of amyloid and tau were assessed. Statistical Tests: Multiple linear regression analyses of OEF with diagnostic category (normal, MCI, or dementia), vascular risks, cognitive performance, amyloid and tau pathology. Results: When evaluating the entire group, OEF was found to be lower with more severe cognitive impairment (β = −2.70 ± 1.15, T  = −2.34, P = 0.02), but was higher with greater vascular risk factors (β = 1.36 ± 0.55, T = 2.48, P = 0.02). Further investigation of the subgroup of participants with low vascular risks ( N = 44) revealed that lower OEF was associated with worse cognitive performance (β = 0.04 ± 0.01, T = 3.27, P = 0.002) and greater amyloid burden (β = 92.12 ± 41.23, T = 2.23, P = 0.03). Among cognitively impaired individuals ( N = 40), higher OEF was associated with greater vascular risk factors (β = 2.19 ± 0.71, T = 3.08, P = 0.004). Data Conclusion: These findings suggest that OEF is differentially affected by Alzheimer's disease and VCI pathology and may be useful in etiology‐based diagnosis of cognitive impairment. Level of Evidence: 1 Technical Efficacy: Stage 3 J. MAGN. RESON. IMAGING 2020;52:1829–1837.